2012
DOI: 10.4314/ijbcs.v6i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of pre-supplementation with selenium on cadmium-induced oxidative damage to some rat tissues

Abstract: The effect of the antioxidant nutrient selenium, Se, on biologic response to cadmium-induced oxidative cytotoxicity was investigated in rats pretreated with Se prior to exposure to mild doses of Cd. Male wistar strain rats (200-250 g b.wt) were exposed to a single daily oral dose of cadmium (3 mg CdCl 2 /kg) in drinking water for five days following a 15-day oral supplementation with Se (3.0 or 3.5 mg SeO 2 /kg/day) in drinking water at the end of which membrane lipid peroxidation, ascorbic acid and glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
13
7
0
Order By: Relevance
“…However, pretreatment with aqueous leaf extract of Vitex doniana alters the pattern of Cd disposition and markedly reduced the level of bioaccumulation of Cd in the rat liver and kidney. This is in agreement with the previous studies which showed that oral intake of cadmium induces its accumulation in these tissues [17]. The decreased cadmium concentration in the liver and kidneys could be explained by its redistribution to other tissues and organs as well as by the formation of cadmium-extract complexes or by interfering with free radical chain initiation and progression of Cd-induced oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, pretreatment with aqueous leaf extract of Vitex doniana alters the pattern of Cd disposition and markedly reduced the level of bioaccumulation of Cd in the rat liver and kidney. This is in agreement with the previous studies which showed that oral intake of cadmium induces its accumulation in these tissues [17]. The decreased cadmium concentration in the liver and kidneys could be explained by its redistribution to other tissues and organs as well as by the formation of cadmium-extract complexes or by interfering with free radical chain initiation and progression of Cd-induced oxidative damage.…”
Section: Discussionsupporting
confidence: 93%
“…The role of antioxidants is to neutralize the excess of free radicals, to protect the cells from toxic effects and to contribute to disease prevention [7,11]. This has been demonstrated in experimental cadmium intoxication where certain micronutrients antioxidants notably, vitamin E and selenium, have reportedly reversed or prevented cadmium toxicity to target tissue cells [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of H. sabdariffa anthocyanins to protect and liver and other tissues is shown by the significant (P<0.05) increase in the activity of CAT and SOD in the liver and other tissues when compared with rats exposed to Cd alone. This again shows that H. sabdariffa anthocyanins are potent antioxidant and is in consonance with the reported protective effects of antioxidant nutrients against Cd-induced oxidative stress and lipid peroxidation in the liver and kidney (Asagba et al, 2010and Mafulul andOkoye, 2012).…”
Section: Orororo Oc; Asagba So; Tonukari Nj; Okandeji Oj; Mbanugosupporting
confidence: 57%
“…Baiomy, (2016 showed that Cd caused increase in lung tissue malondialdehyde and reduced the activity of glutathione peroxidase and other antioxidant enzymes, while the work of Al Groom and Al-Kubaisy (2016) indicated that Cd administration significantly reduced glutathione (GSH) concentration, but increased malondialdehyde levels in rat erythrocytes. Membrane lipid peroxidation has been shown as an important early manifestation of Cdinduced oxidative damage to the liver and kidney playing a major role in the induction of toxic lesions Okoye, 2012 andEmbugushiki et al, (2013). This study confirms that exposure to cadmium causes a significant increase in membrane lipid peroxidation in the liver and kidneys of rats.…”
Section: Effects Of Hibiscus Sabdarrifa L…mentioning
confidence: 99%
“…Heavy metals are a class of chemicals known for their very risky and dangerous nature as slight carelessness in their handling could be indicative of very significant fatal experiences [1,2]. Cadmium which belongs to a class of these chemicals is said to be one of the most dangerous of them as it bio accumulates [3,4] when it eventually builds up in high concentrations, contributes significantly to the gradual shut down and deterioration of most biological systems due to the high affinity it has for the liver and kidney [5,6]. The mechanism of cadmium toxicity has been reported to involve reduction in the functionality of cell membrane binding to the ion transporter metallothionein, as well as the glutathione cascade which eventually affects the maintenance of cell membrane integrity and the inhibition of oxidative stress [7,8].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%